Combination of ultrasonography and tongue depressor for predicting difficult laryngoscopy in apparently normal patients. Issue 3 (September 2022) - Li, Dewei; Zhao, Gaofeng; Zeng, Chaokun; Liu, Huiming; Zhong, Min; Li, Jie; Lin, Chunshui
Abstract: Objectives: We hypothesized measurements of the upper airway using ultrasound and a tongue depressor can be used to predict difficult laryngoscopy. Methods: There were 239 patients enrolled. The receiver operating characteristic curve (ROC) analysis was used to assess the diagnostic value of clinical parameters, sonographic parameters, and multivariable models. Results: 26 (10.9%) of the patients had difficult laryngoscopy. Age, sex, modified Mallampati score, interincisor gap, thyromental distance, distances from arytenoids and hyoids (DDHB) to the tongue depressor, and angle between the tongue depressor and the line of vision all had statistically significant differences ( P  ≤ 0.002). At a cutoff value of 2.76 cm, DDHB demonstrated relatively good diagnostic value (sensitivity 73.1 percent, specificity 93 percent) and increased the area under the ROC of the clinical parameters model from 0.871 to 0.943 (P = 0.027). Conclusions: DDHB is an independent predictor of difficult laryngoscopy and improves the clinical parameters model's diagnostic value.